2008
DOI: 10.1007/s11095-008-9668-2
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Renal Organic Ion Transporters in Cisplatin-Induced Acute Kidney Injury and Uremia in Rats

Abstract: Cisplatin-induced AKI causes down-regulation of renal organic ion transporters accompanied by accumulation of serum and renal IS. IS could be involved in the mechanism of down-regulation of rOAT1, rOAT3 and rMATE1 under cisplatin-induced AKI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 30 publications
(52 reference statements)
1
26
0
Order By: Relevance
“…On the other hand, rOCT2 expression was down-regulated 120 h after CDDP treatment in the low Mg group. We previously reported that protein expression levels and the activity of rOCT2 were markedly decreased by CDDP-induced AKI and ischemia/reperfusion-induced AKI [22,23]. Using 5/6 nephrectomized rats, Ji et al [24] reported that renal clearance of unbound cimetidine, a substrate of rOCT2, and the expression levels of rOCT2 were correlated.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, rOCT2 expression was down-regulated 120 h after CDDP treatment in the low Mg group. We previously reported that protein expression levels and the activity of rOCT2 were markedly decreased by CDDP-induced AKI and ischemia/reperfusion-induced AKI [22,23]. Using 5/6 nephrectomized rats, Ji et al [24] reported that renal clearance of unbound cimetidine, a substrate of rOCT2, and the expression levels of rOCT2 were correlated.…”
Section: Discussionmentioning
confidence: 96%
“…AST-120, an oral charcoal adsorbent, reduced IS concentrations in the blood and inhibited oxidative stress in rats [23]. Previously, we reported that administration of AST-120 significantly decreased IS accumulation in the serum and kidney, and also ameliorated cisplatin-induced AKI [11,12]. We suggested that IS accelerated cisplatin-induced AKI as a key mediator, and that AST-120 treatment may be useful in preventing the progression of renal dysfunction by decreasing IS accumulation in the kidney.…”
Section: Discussionmentioning
confidence: 97%
“…We previously reported that indoxyl sulfate (IS), a typical uremic toxin generated in the liver, might be involved in the progression of cisplatin-induced AKI [11][12][13]. Several reports also showed that IS had potential of oxidative stress to the kidney.…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatininduced acute kidney injury resulted in elevated serum levels of the uremic toxin, indoxyl sulfate. In addition, cisplatin was shown to reduce renal OAT function as measured by PAH and estone sulfate uptake in kidney slices [140]. Accordingly, mRNA and protein of rOat1 and rOat3 were reduced in the kidney.…”
Section: Pharmacotherapeutics and Natural Productsmentioning
confidence: 96%
“…Leucovorin circumvented this inhibition by providing a source of reduced folate that can be readily converted to the tetrahydrofolate necessary for DNA synthesis. In a different study, the commonly prescribed nephrotoxic anticancer drug, cisplatin, was assessed in rats [140]. Cisplatininduced acute kidney injury resulted in elevated serum levels of the uremic toxin, indoxyl sulfate.…”
Section: Pharmacotherapeutics and Natural Productsmentioning
confidence: 99%